Development of technologies applied to the biodegradation of warfare nerve agents: Theoretical evidence for asymmetric homogeneous catalysis. (1st August 2019) - Pereira, Ander Francisco; de Castro, Alexandre A.; Soares, Flavia Villela; Soares Leal, Daniel Henriques; da Cunha, Elaine F.F.; Mancini, Daiana Teixeira; Ramalho, Teodorico C.
Abstract: Organophosphorus compounds have been widely employed to the development of warfare nerve agents and pesticides, resulting in a huge number of people intoxicated annually, being a serious problem of public health. Efforts worldwide have been done in order to design new technologies that are capable of combating or even reversing the poisoning caused by these OP nerve agents. In this line, the bioremediation arises as a promising and efficient alternative for this purpose. As an example of degrading enzymes, there is the organophosphate-degrading (OpdA) enzyme from Agrobacterium radiobacter, which has been quite investigated experimentally due to its high performance in the degradation of neurotoxic nerve agents. This work aims to look into the structural and electronic details that govern the interaction modes of these compounds in the OpdA active site, with the posterior hydrolysis reaction prediction. Our findings have brought about data about the OpdA performance towards different nerve agents, and among them, we may realize that the degradation efficiency strongly depends on the nerve agent structure and its stereochemistry, being in this case the compound Tabun the one more effectively hydrolyzed. By means of the chemical bonds (AIM) and orbitals (FERMO) analysis, it is suggested that the initial reactivity of the OP nerve agents in the OpdA active site does not necessarily dictate the reactivity and interaction modes over the reaction coordinate. Highlights: The OpdA enzyme was effective in the degradation process of the GA/GD/GB agents. The degradation of the OP agents depends on their structures and stereochemistry. The Tabun nerve agent was more efficiently hydrolyzed. AIM and FERMO analyses not necessarily dictate the reactivity and interaction.